1998
DOI: 10.1093/intimm/10.4.491
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 is required for the induction of high dose oral tolerance

Abstract: Mucosal and systemic administrations of high dose antigens induce long-lasting peripheral T cell tolerance. We and others have shown that high dose peripheral T cell tolerance is mediated by anergy or deletion and is preceded by T cell activation. Co-stimulatory molecules B7-1 (CD80)/B7-2 (CD86) and their counter-receptors CD28/CTLA-4 play pivotal roles in T cell activation and immune regulation. In the present study, we examined the roles of the B7 co-stimulation pathway in the generation of high dose periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 48 publications
6
56
3
Order By: Relevance
“…It has been suggested that CTLA-4 is required for oral tolerance induction. However, this remains controversial because it has been reported that CTLA-4 blockade can abolish oral tolerance induced by oral exposure to OVA (9,10,24), while others have reported that CTLA-4 blockade failed to overcome development of oral tolerance to OVA in a similar model (25). In the present model, mice orally exposed to peanut without adjuvant do not develop PPE-specific IgE and only very low IgG responses.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It has been suggested that CTLA-4 is required for oral tolerance induction. However, this remains controversial because it has been reported that CTLA-4 blockade can abolish oral tolerance induced by oral exposure to OVA (9,10,24), while others have reported that CTLA-4 blockade failed to overcome development of oral tolerance to OVA in a similar model (25). In the present model, mice orally exposed to peanut without adjuvant do not develop PPE-specific IgE and only very low IgG responses.…”
Section: Discussionmentioning
confidence: 54%
“…Although very little is known about the role of the CD28-CTLA-4/B7 pathway in food allergy, anti-CTLA-4 treatment has been shown to abrogate systemic hyporesponsiveness to orally administered OVA in oral tolerance models (9,10). This suggests that CTLA-4 signaling might be decisive in oral tolerance development.…”
mentioning
confidence: 99%
“…Although the nature of the second signal is still under intense investigation, B7-mediated costimulation has been considered to be the most likely candidate. However, recent reports from several laboratories including ours indicate that B7 may also be required for the induction of T cell tolerance, and that B7:CTLA4 interaction is essential for maintaining peripheral T cell tolerance (31)(32)(33)(34)(35). Thus, it appears that the costimulatory molecule B7 may be required for the development of both immunity and tolerance.…”
mentioning
confidence: 84%
“…Both CTL-associated antigen (CTLA)-4 and programmed death-1 (PD1) are markers that are associated with the suppressive capacity of naturally occurring Tr cells [28][29][30][31]. For PD1 no staining above background could be found on antigenspecific T cells (data not shown), whereas for CTLA-4 increased expression was only found on cells that had divided six or seven times at 72 h (Fig.…”
Section: Ctl-associated Antigen-4 Programmed Death-1 and > 4 I 7 Expmentioning
confidence: 99%